If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(m+6)=2m
We simplify the equation to the form, which is simple to understand
3(m+6)=2m
Reorder the terms in parentheses
+(+3m+18)=2m
Remove unnecessary parentheses
+3m+18=+2m
We move all terms containing m to the left and all other terms to the right.
+3m-2m=-18
We simplify left and right side of the equation.
+1m=-18
We divide both sides of the equation by 1 to get m.
m=-18
| 24/8= | | 3n^2-6n-1=0 | | -5(x-1)=20(x-10) | | 2000*0.75= | | -12.42=.03p | | 7-4x=3x+35 | | g-4=-13 | | 5(a+3b)=5a+15b | | x^2-16y=0 | | 5*16*15=b | | 5x-8=7x+12x | | y=4x-q | | -13+q=-40 | | 4(a+b)+6(b+2a)= | | 5.16.15=b | | 9.6m+6=300.5 | | h+2=13 | | -3x-71=103-9x | | 2(4v+9)=98 | | 4q+2q+3=6q-4 | | 6a+(-2c)+(-4a)+c= | | 2x^2-96=x | | 13x+15=13x-15 | | S-3=5s | | 7(7+2l)=3(9l-1) | | 1gh-4gh+7g-8h+h= | | (-3)y+4+5y=(-6) | | 8x+44=4x-12 | | 4x^2+32+5=0 | | 3.5x-8=58.5 | | -x-71=89-11x | | x=3.4+0.2y |